Perilaku Konsumtif dan Belanja Online: Sebuah Analisis Hukum Islam - Budiman, Arif; Ariyadi, Ariyadi; Hidayat, Heru; Khasanah, Kusnia Nikmatul (Lembaga Yasin AlSys, 2025)
This research is motivated by the limited research on Islamic law related to consumptive behavior in online shopping. This study aims to analyze the consumptive behavior of students in online shopping activities in terms of the principles of Islamic law. This research adopts a normative-empirical approach through semi-structured interviews with students of IAIN Palangka Raya with a sample of 5 people randomly selected, as well as adopting literature studies from relevant journals published in 2023-2025. Data were collected using interview instruments and literature data were obtained through publish or perish and the data used were journals related to consumptive attitudes in online shopping related to Islamic law. The findings reveal that online shopping encourages consumptive behavior, but can be controlled through self-efficacy, understanding of Islamic law, and good financial literacy. The study concluded that the level of self-efficacy and understanding of Islamic economic values is very influential in suppressing excessive consumptive behavior. Students who have good self-control and sharia insight tend to shop wisely and responsibly. Thus, it is necessary to strengthen financial literacy and understanding of Islamic law so that people, especially students, can utilize online shopping in a balanced manner and in accordance with religious values. Opportunities that can be taken by future researchers can continue to examine the consumptive behavior of students in the long term, such as what the impact is before and after being given Islamic-based financial literacy education.